2021
DOI: 10.1002/smll.202104855
|View full text |Cite
|
Sign up to set email alerts
|

Rare‐Earth Doped Iron Oxide Nanostructures for Cancer Theranostics: Magnetic Hyperthermia and Magnetic Resonance Imaging

Abstract: He received his Ph.D. degree in materials sciences from the University of South Australia and his research primarily focuses on carbon capture using nanoporous materials. He has published 39 articles including review and research articles in high-quality materials science-based journals including Chemical Society Reviews and Advanced Materials. His contribution to the research has been acknowledged in the form of 1580 google scholar citations with an h-index of 18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 225 publications
(421 reference statements)
1
34
0
Order By: Relevance
“…Thus, the net magnetization of EuMZF is governed by the cation distribution of Fe 3+ , Mn 2+ and Zn 2+ ions in A and B sites. It was shown that rare-earth ions prefer to occupy the octahedral B sites due to their larger ionic radii [ 56 ]. As Eu 3+ ions enter the B sites, some Fe 3+ ions are replaced and forced to migrate to the A sites.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the net magnetization of EuMZF is governed by the cation distribution of Fe 3+ , Mn 2+ and Zn 2+ ions in A and B sites. It was shown that rare-earth ions prefer to occupy the octahedral B sites due to their larger ionic radii [ 56 ]. As Eu 3+ ions enter the B sites, some Fe 3+ ions are replaced and forced to migrate to the A sites.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, the nanomaterials have been hugely exploited for advanced biomedical applications [ 141 , 142 , 143 , 144 , 145 ]. As already stated, mostly nano-ferrites and metal oxide nanomaterials as well as graphene oxides and carbon nanotubes show intrinsic peroxidase-like activities [ 111 , 116 , 117 , 146 , 147 ].…”
Section: Nanomaterials Based Sensingmentioning
confidence: 99%
“…For that reason, RE doped nanoferrites are suitable for hyperthermia applications (Martinez-Boubeta et al, 2013). RE-doped Fe 3 O 4 shows higher magnetic-moments and a relatively larger diameter (S. S. Laha et al, 2022). Also, it shows stronger spin-orbit-coupling which is responsible for causing strain in Fe 3 O 4 lattice thereby, enhancing the anisotropy and magnetization.…”
Section: Iron-oxide Based Nanomaterials Used For Magnetic Hyperthermiamentioning
confidence: 99%
“…Various organic/inorganic polymers, biopolymers and surfactants, such as polyethylenegylcol (PEG), polyvinyl alcohol (PVA), dextran, chitosan, polyvinyl pyrrolidone (PVP), oleic acid and hyaluronic acid (HA), have been explored to carry out physical coating/functionalization (S. S. Laha et al, 2022). Various polymers used and the polymer type (end-grafted, surface adsorbed, phospholipids and di-block or co-polymers) are shown in Figure 11.…”
Section: Physical Modificationmentioning
confidence: 99%